Extended Rayleigh Damping Model - Nakamura, Naohiro (Frontiers in Built Environment, 2016)
In dynamic analysis, frequency domain analysis can be used if the entire structure is linear. However, time history analysis is generally used if non-linear elements are present. Rayleigh damping has been widely used in time history response analysis. Many articles have reported the problems associated with this damping and suggested remedies. A basic problem is that the frequency area across which the damping ratio is almost constant is too narrow. If the area could be expanded while incurring only a small increase in computational cost, this would provide an appropriate remedy for this problem. In this study, a novel damping model capable of expanding the constant frequency area by more than five times was proposed based on the study of a causal damping model. This model was constructed by adding two terms to the Rayleigh damping model and can be applied to the linear elements in the time history analysis of a non-linear structure. The accuracy and efficiency of the model were confirmed using example analyses.